A macroscopic violation of no-signaling in time inequalities? How to test temporal entanglement with behavioral observables - Tressoldi, Patrizio E.; Maier, Markus A.; Buechner, Vanessa L.; Khrennikov, Andrei (Frontiers in Psychology, 2015)
In this paper we applied for the first time the no-signaling in time (NSIT) formalism discussed by Kofler and Brukner to investigate temporal entanglement between binary human behavioral unconscious choices at t1 with binary random outcomes at t2. NSIT consists of a set of inequalities and represents mathematical conditions for macro-realism which require only two measurements in time. The analyses of three independent experiments show a strong violation of NSIT in two out of three of them, suggesting the hypothesis of a quantum-like temporal entanglement between human choices at t1 with binary random outcomes at t2. We discuss the potentialities of using NSIT to test temporal entanglement with behavioral measures.